Preliminary biochemical studies on a model growing of different tobacco plant (Nicotiana tabacum L.) cultivars - Szedljak, I.; Szántainé Kőhegyi, K.; Kosáry, J. (International Journal of Horticultural Science, 2007)
The aim of our preliminary studies was to characterize the change in the activity of enzymes PPO and PDX, the concentration of total soluble phenolic compounds and soluble protein content of different tobacco cultivars measured in tobacco plants during cultivation. The results suggest that a shorter cultivation period (13-14 weeks) is more favourable for tobacco plants as protein source than for tobacco industrial use (16-17 weeks). We found some correlation between the concentration of total soluble phenolic compounds and PPO activity data. In the increasing and maximum period of total phenol content the PPO activity was high. But later because of decrease of substrate phenol content the activity of PPO also decreased. We found higher soluble protein concentrations in Virginia than in Burley varieties.